1987
DOI: 10.3354/meps041087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flooding and salinity on photosynthesis of Sagittaria lancifolia

Abstract: Sagittaria lancifolia L, plants were subjected to floodmg, salmity, and combined treatments. Effects of each treatment and their interaction on stomatal conductance and net photosynthesis were evaluated after 4 wk of acclimation to the imposed condtions. Effect of floohng on leaf conductance was not significant while the sahnity effect was significant. Both flooding and salinity reduced net photosynthesis significantly. However, their interaction was not significant. The stomata1 limitation of photosynthesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
(16 reference statements)
0
18
1
Order By: Relevance
“…The reduced net photosynthesis found for this species in a greenhouse study by Pezeshki et al (1987) after about 2 months exposure to 5 cm of increased freshwater flooding is apparently a shortterm response that does not affect biomass accumulation. Additional evidence for the ability of this species to adapt to flooding stress was provided in the field study by McKee and Mendelssohn (1989), where a 10-cm increase in water depth was found to have no effect on biomass or stem density after one growing season.…”
Section: Environmental Responsementioning
confidence: 99%
“…The reduced net photosynthesis found for this species in a greenhouse study by Pezeshki et al (1987) after about 2 months exposure to 5 cm of increased freshwater flooding is apparently a shortterm response that does not affect biomass accumulation. Additional evidence for the ability of this species to adapt to flooding stress was provided in the field study by McKee and Mendelssohn (1989), where a 10-cm increase in water depth was found to have no effect on biomass or stem density after one growing season.…”
Section: Environmental Responsementioning
confidence: 99%
“…Subsidence accounts for 85 to 90 percent of relative sea level rise and the remaining portion is attributed to the 0.1-0.2 cm year Ϫ1 rise of eustatic sea level (DAY and TEMPLET, 1989). Increasing sea level will increase submergence potential and salinity level, which will directly affect coastal wetland viability (SALINAS et al, 1986;DELAUNE et al, 1987). The low tidal range of the Gulf of Mexico provides a narrow elevation gradient in which coastal marshes can survive and makes Louisiana's wetlands more susceptible to sea level rise (DAY et al, 1995;STUMPF and HAINES, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several short-term investigations, from as short as 35 days (MCKEE and MENDELSSOHN, 1989) to as long as 15 months (HOWARD and MENDELSSOHN, 1995), both in greenhouse and field studies have examined the effects of salinity (HOWARD and MENDELSSOHN, 1999a,b), of flooding (HOWARD and MEN- DELSSOHN, 1995), and both salinity and flooding on the growth of S. lancifolia (PEZESHKI et al, 1987;MCKEE and MENDELS-SOHN, 1989;FLYNN et al, 1995;WEB and MENDELSSOHN, 1996;BALDWIN and MENDELSSOHN, 1998a). Those greenhouse studies, previously mentioned, utilized a single species of Sagittaria (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Broadleaf marshes of the southeastern United States are defined by dominance of species with flag-like leaves, principally Sagittaria lancifolia, Pontederia cordata and Thalia geniculata (Davis 1943;Winchester et al 1985;Pezeshki et al 1987;Botts and Cowell 1988;Webb and Mendelssohn 1996). Broadleaf marshes are most commonly found in south and central Florida and southern Louisiana (Penfound 1952) in wetlands with prolonged annual inundation (i.e., hydroperiods >200 days per year) and wet season depths of 1 m or more (Kushlan 1990).…”
Section: Introductionmentioning
confidence: 99%